Establishing volume load parameters: A different look in designing a strength training periodization for throwing events - Oliveto, N. (Strength and Conditioning Journal, 2004)
This article suggests a way to establish throwing events volume load parameters and to incorporate these data into a resistance-training periodization designed by the strength coach. The method of calculating the throwing volume can be beneficial for a strength and conditioning professional looking for insightful information about an athlete's magnitude of throwing training outside the weight room.